Is the profession of dentistry losing its yesteryear's glory? An exploratory study from dental students' perspective - Vikram Simha Bommireddy; Viswa Chaitanya Chandu; Harish Chowdary Kommineni; Anu Vijaykumar; Srinivas Ravoori; Gayathri Spandana Neeli (Wolters Kluwer Medknow Publications, 2021)
Introduction: The regard for dentistry as a profession has been declining over the recent years in light of the increasing number of dental students graduating per year with negligible improvement in the utilization of oral health care services. In this context, it is important to document the perceptions and apprehensions of the current dental students as these feelings would have an influence on the roles they assume as dentists in future. Aim: With this background, this study attempts to document the willingness of dental students from three South Indian states to re-choose dentistry given an opportunity. Materials and Methods: This cross-sectional survey was conducted among house surgeons from 12 dental institutions, 4 each from the southern Indian states of Andhra Pradesh, Telangana, and Tamilnadu. The semi-structured questionnaire used in this study consisted of five primary questions along with details on the participants' gender, type of admission. It aimed at documenting the willingness to re-choose dentistry given an opportunity, and the reasons for their willingness or otherwise. A total of 822 students constituted the final sample. SPSS version 20 software was used to analyse the data. Results: Majority of the study participants were from Tamil Nadu, not reported dentistry as their primary career choice, and demonstrated reluctance in re-choosing dentistry given an opportunity. A significantly higher percentage of dental students from Tamil Nadu reported dentistry as their first professional choice. This observation persisted in the response of students for the question on their willingness to re-choose dentistry. Conclusion: The study results demonstrate the declining interest and regard for dentistry among the current dental students with nominal variations between students from the three South Indian states.